An equation for estimating low-density lipoprotein-triglyceride content and its use for cardiovascular disease risk stratification - Wolska, Anna; Sampson, Maureen; Zubirán, Rafael; Meeusen, Jeff W.; Donato, Leslie J.; Jaffe, Allan S.; Remaley, Alan T. (Frontiers in Cardiovascular Medicine, 2024)
Background: The triglyceride (TG) content of low-density lipoprotein (LDL-TG) has been shown to be more predictive of atherosclerotic cardiovascular disease (ASCVD) events than the cholesterol content of LDL (LDL-C). The goal of our study was to develop an equation for estimating LDL-TG (eLDL-TG) based on the standard lipid panel and to compare it to estimated LDL-C as an ASCVD risk biomarker. Methods: Using least-square regression analysis, the following eLDL-TG equation was developed: eLDL ̵TG=TG/38.5+(NonHDL¬ ̵C)/5.75+(9.75 TG)/(NonHDL ̵¬C)+244/(HDL¬ ̵C)-2.95. LDL-TG was measured by the β-quantification (BQ) reference method (N=40,202). LDL-C was calculated by the Sampson-NIH equation. The association of LDL-C and eLDL-TG with ASCVD risk markers was performed in the National Heart and Nutrition Examination Survey (NHANES) (N=37,053) and with ASCVD events in a primary prevention cohort from the UK Biobank (UKB) (N=429,367) and the Atherosclerosis Risk in Communities (ARIC) study (N=14,632). Results: eLDL-TG showed better ASCVD risk stratification of UKB participants than LDL-C (Wilcoxon Chi-Square: 2099.6 vs. 418.7, respectively). Receiving-operating characteristics analysis revealed that eLDL-TG had a stronger association with ASCVD events than LDL-C (AUC: 0.596 vs. 0.542, respectively) and other conventional lipid markers. Similar findings were found in ARIC. Discordance analysis in UKB showed that the group with low LDL-C/high eLDL-TG had a similar risk as the high LDL-C/high eLDL-TG group. Furthermore, these same two groups with the highest eLDL-TG levels and the highest ASCVD event rate also had higher mean levels of systolic blood pressure, Body Mass Index, hemoglobin A1C, and C-reactive protein than the two lower eLDL-TG groups. Using eLDL-TG >44.6 mg/dL (80th percentile) as a cut-point leads to a hazard ratio of 1.32 (95% CI, 1.29-1.36) for ASCVD events, which remained significant after adjustment for LDL-C and apoB. Furthemore, using eLDL-TG as a risk-enhancer test leads to reclassification of 50% more high-risk individuals than current lipid-enhancer test rules. Conclusions: Like LDL-C, LDL-TG can also be calculated from the results of the standard lipid panel. Compared to estimated LDL-C, eLDL-TG was a better risk marker for primary prevention and hence could improve initial ASCVD risk stratification.